Christian Hope in Context II - Egmond, A. van,; Keulen, Dirk van, (Studies in Reformed Theology;, 2001)
The International Reformed Theological Institute (IRTI) was founded in 1995. Its purpose is to create a platform where Reformed theologians from all over the world can meet each other, become acquainted with each other's work, discuss theological issues and stimulate each other in scholarly theological research. The members of IRTI present their work in the series Studies in Reformed Theology . Thus, the volumes of this series offer a perspective on the theological insights and spirituality of Reformed theologians all over the world. The fourth and fifth volume of the series Studies in Reformed Theology contain the contributions to the third international conference of the IRTI. Leading theme of the conference was 'Christian Hope in Context.' This fifth volume contains contributions form the different African and Asian perspectives. Other articles reflect the ecological crisis, feminist theology and Ecumenism. At the end of this volume the devotional contributions to the conference may be found. All articles and contributions in one way or another reflect the context of the author.